Composition and Conservation Status of Avifauna in Urban Non-protected Important Bird Area (IBA) Site of Western India - Makwana, Vishal M.; Khatsuriya, Prakruti A.; Matli, Aamir G.; Dodia, Pravinsang P. (Universitas Gadjah Mada, 2024)
Kumbharwada wetland, an Important Bird Area (IBA) component in Bhavnagar, Gujarat, India, is a crucial wintering ground for migratory birds. Long-term monitoring of the avian community over a period of long time-frame is an excellent way to examine the health of this IBA site and thus provide an important ground to foster the conservation of birds in the region and management of this wetland. Given this consideration, field surveys were carried out from December 2020 to May 2023, following point count method to study the avian species richness in the study area. A total of 204 bird species belonging to 20 orders and 56 families are recorded, of which 85 species are migratory and 119 are resident. Anatidae is the most species-rich avian family (16 species). Highest number of species was recorded in the month of January (165 species in 2021 and 163 species in 2022). This wetland supports 107 (52.45%) wetland-associated species and 97 (47.55%) terrestrial species of birds. Twelve species are considered as Near Threatened, four species as Vulnerable and one species (Aquila nipalensis) as Endangered in IUCN Red List of Threatened Species. Four species (Sterna aurantia, Mycteria leucocephala, Phoeniconaias minor, and Threskiornis melanocephalus) with globally declining trend, are commonly seen in the study area, which shows that the wetland is a crucial habitat for bird species with high conservation priorities. Industrialization, encroachment, discharge of sewage water and chemical effluents, high-tension powerlines, stray dogs, and expansion of exotic vegetation remained the major threats to the habitat and avian community.